Structurally graduated collagen scaffolds applied to the ex vivo generation of platelets from human pluripotent stem cell-derived megakaryocytes: Enhancing production and purity. (November 2018) - Shepherd, Jennifer H.; Howard, Daniel; Waller, Amie K.; Foster, Holly Rebecca; Mueller, Annett; Moreau, Thomas; Evans, Amanda L.; Arumugam, Meera; Bouët Chalon, Guénaëlle; Vriend, Eleonora; Davidenko, Natalia; Ghevaert, Cedric; et al.
Abstract: Platelet transfusions are a key treatment option for a range of life threatening conditions including cancer, chemotherapy and surgery. Efficient ex vivo systems to generate donor independent platelets in clinically relevant numbers could provide a useful substitute. Large quantities of megakaryocytes (MKs) can be produced from human pluripotent stem cells, but in 2D culture the ratio of platelets harvested from MK cells has been limited and restricts production rate. The development of biomaterial cell supports that replicate vital hematopoietic micro-environment cues are one strategy that may increase in vitro platelet production rates from iPS derived Megakaryocyte cells. In this paper, we present the results obtained generating, simulating and using a novel structurally-graded collagen scaffold within a flow bioreactor system seeded with programmed stem cells. Theoretical analysis of porosity using micro-computed tomography analysis and synthetic micro-particle filtration provided a predictive tool to tailor cell distribution throughout the material. When used with MK programmed stem cells the graded scaffolds influenced cell location while maintaining the ability to continuously release metabolically active CD41  +  CD42  +  functional platelets. This scaffold design and novel fabrication technique offers a significant advance in understanding the influence of scaffold architectures on cell seeding, retention and platelet production.